2008
DOI: 10.1104/pp.108.131755
|View full text |Cite
|
Sign up to set email alerts
|

The Cauliflower Mosaic Virus Protein P6 Forms Motile Inclusions That Traffic along Actin Microfilaments and Stabilize Microtubules    

Abstract: The gene VI product (P6) of Cauliflower mosaic virus (CaMV) is a multifunctional protein known to be a major component of cytoplasmic inclusion bodies formed during CaMV infection. Although these inclusions are known to contain virions and are thought to be sites of translation from the CaMV 35S polycistronic RNA intermediate, the precise role of these bodies in the CaMV infection cycle remains unclear. Here, we examine the functionality and intracellular location of a fusion between P6 and GFP (P6-GFP). We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
104
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(112 citation statements)
references
References 89 publications
7
104
0
1
Order By: Relevance
“…3A), whereas P6-GFP formed well-defined P6-GFP I-LBs of varying sizes (Fig. 3B) as previously described (Harries et al, 2009a;Angel et al, 2013). Upon coagroinfiltration of AtSRC2.2-RFP with P6-GFP into leaf panels of N. benthamiana, the AtSRC2.2-RFP protein was frequently colocalized with P6-GFP in both small and large aggregates (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…3A), whereas P6-GFP formed well-defined P6-GFP I-LBs of varying sizes (Fig. 3B) as previously described (Harries et al, 2009a;Angel et al, 2013). Upon coagroinfiltration of AtSRC2.2-RFP with P6-GFP into leaf panels of N. benthamiana, the AtSRC2.2-RFP protein was frequently colocalized with P6-GFP in both small and large aggregates (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Ectopic expression of a P6-GFP fusion protein in N. benthamiana had shown that P6-GFP I-LBs were capable of associating with and moving on microfilaments (Harries et al, 2009a). Furthermore, treatment of plant tissues with latrunculin B blocked the development of CaMV local lesions in N. edwardsonii.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations